Creating a racially polarized electorate: the political fallout of immigration politics in Arizona and California. (1st October 2016) - Robinson, Gregory; Krasno, Jonathan S.; Zingher, Joshua N.; Allen, Michael A.
Abstract : We explore the potential political impact of Arizona's controversial immigration statute, SB 1070, using a parallel event: the 1994 passage of Proposition 187 in California. Both statutes were efforts to respond to the flow of illegal immigrants mainly from Mexico and were widely seen as anti-Latino, and both became the central theme of their proponents' reelection campaigns. We reexamine and extend the academic literature on the political impact of Proposition 187, applying the effect estimates to Arizona via a Monte Carlo simulation to project its vote in future presidential elections. These projections show that the potential changes in voting behavior brought on by SB 1070, coupled with population trends, give Democrats a discernable and growing advantage in presidential elections as early as 2016. The results of 2012 make clear that the GOP's best hope to hold the state rests on a strong and enduring move by its white voters toward the Republicans, leaving Arizona with a racially polarized electorate more reminiscent of the American South than its Southwest. We speculate about the potential to create such an electorate where an unusually large percentage of white voters immigrated there as adults from other states.